High-Density Adaptive Ten Ten: Proposal for Electrode Nomenclature for High-Density EEG. Issue 3 (May 2020) - Heine, Walter; Dobrota, Mary-Ann; Schomer, Donald; Wigton, Rebekah; Herman, Susan
Abstract : Purpose: High-density EEG (HD-EEG) systems and electrical source imaging techniques have revolutionized our ability to assess the potential sources of epileptiform activity and other EEG features. Nonetheless, clinical use of HD-EEG is hampered by the lack of a standardized electrode nomenclature system and the inherent difficulties encountered in visually reviewing recordings. Inefficient visual review of HD-EEG remains a major barrier to incorporating these techniques into routine clinical care. Methods: Extension of the 10-10 is first defined by the addition of 2 reference curves: the −10% and −20% axial reference curves. Electrode positions over the face are named based on facial bony structures (N = nasion, Z = zygomatic prominence, M = mandible) and over the back of the head on posterior landmarks (I = inion, S = subinion, B = Base). Then, following the 10% incremental distance rule, we define additional electrode positions. Electrodes with nonstandard positions are clustered around the closest 10-10 electrode, deemed their cardinal point. Results: The 256-electrode Geodesic Sensor Net mapped to 96 of the 120 extended 10-10 cardinal electrodes. Conclusions: Electrode position nomenclature that builds upon the international standard 10-10 system allows electroencephalographers to identify spatial areas of interest in HD-EEG relative to positions in routine use. A standard viewing montage for HD-EEG and its application with electrical source imaging boost efficiency when reviewing data and improve accuracy in recognizing epileptiform discharges. Additionally, our proposed system is not limited to a specific HD-EEG system, electrode count, or electrode layout. Abstract : Supplemental Digital Content is Available in the Text.